Recent Initiatives in the Republic of Srpska to Enhance Appropriate Use of Antibiotics in Ambulatory Care; Their Influence and Implications - Bojanić, Ljubica; Marković-Peković, Vanda; Škrbić, Ranko; Stojaković, Nataša; Ðermanović, Mirjana; Bojanić, Janja; Fürst, Jurij; Kurdi, Amanj B.; Godman, Brian (Frontiers in Pharmacology, 2018)
Introduction:There are increasing concerns world-wide with growing rates of antibiotic resistance necessitating urgent action. There have been a number of initiatives in the Republic of Srpska in recent years to address this and improve rational antibiotic prescribing and dispensing despite limited resources to fund multiple initiatives. Objective: Analyse antibiotic utilization patterns in the Republic of Srpska following these multiple initiatives as a basis for developing future programmes in the Republic if needed. Methods: Observational retrospective study of total outpatient antibiotic utilization from 2010 to 2015, based on data obtained from the Public Health Institute, alongside documentation of ongoing initiatives to influence utilization. The quality of antibiotic utilisation principally assessed according to ESAC, ECDC and WHO quality indicators and DU 90% (the drug utilization 90%) profile as well as versus neighbouring countries. Results: Following multiple initiatives, antibiotic utilization remained relatively stable in the Republic at 15.6 DIDs to 18.4 DIDs, with a decreasing trend in recent years, with rates comparable or lower than neighbouring countries. Amoxicillin and the penicillins accounted for 29%-40% and 50% of total utilization, respectively. Overall, limited utilization of co-amoxiclav (7% - 11%), cephalosporins, macrolides and quinolones, as well as low use of third and fourth generation cephalosporins versus first and second cephalosporins. However, increasing utilization of co-amoxiclav and azithromycin, as well as higher rates of quinolone utilization compared to some countries, was seen. Conclusions: Multiple interventions in the Republic of Srpska in recent years have resulted in one of the lowest utilisation of antibiotics when compared with similar countries, acting as an exemplar to others. However, there are some concerns with current utilisation of co-amoxiclav and azithromycin which are being addressed. This will be the subject of future research activities.